2021
DOI: 10.37547/tajabe/volume03issue02-06
|View full text |Cite
|
Sign up to set email alerts
|

Influence Of New Types Of Horizontal Ditches On The Growth, Development And Yield Of Winter Wheat In Saline And Groundwater Surface Soils

Abstract: The average salinity of Jizzakh region in the vicinity of groundwater (1.5 m) under the influence of a newly built closed bed ditch, winter wheat is irrigated 3 times during the season, the current irrigation rate is 823-933 m3 / ha. The norm of seasonal irrigation was 2586 m3 / ha, and the grain yield of winter wheat was obtained depending on the experimental areas, ie the area of the new construction (experimental variant) and the old type of irrigated area (control). At the same time, the average grain yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Caring for each field crop based on specific soil and climatic conditions is a guarantee of high and quality yields. Under weakly saline soils, no significant change in accumulation was observed when the salt content was 0.3-0.5% by weight of dry soil, all germinated plants were evenly accumulated and healthy seedlings were formed [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Caring for each field crop based on specific soil and climatic conditions is a guarantee of high and quality yields. Under weakly saline soils, no significant change in accumulation was observed when the salt content was 0.3-0.5% by weight of dry soil, all germinated plants were evenly accumulated and healthy seedlings were formed [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…China (202-205 million tons) ranks first in the cultivation of vegetables and fruit products. Countries with developed vegetable production are India (68-75 million tons), USA (34-36 million tons), Turkey (17-21 million tons), Italy (12-15 million tons), Russia (11.5-14.2 million tons), Japan (11-13 million tons) [1,[9][10][11]. Annual production of vegetables per capita is 250-270 kilograms in China, followed by 230-250 in Italy, 150-160 in Poland, 130-145 in the USA, 120-140 in Japan, 90-100 in Ukraine, 86-94 in Russia (Figure 1) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that using it along with planting and during the growing season of vegetables gives higher yield. In fact, the use of herbicides is the most effective way to keep potato and vegetable fields free from weeds, creating favorable conditions for crop development and increasing productivity [10,11]. However, repeated use of one herbicide in one field leads to the proliferation of weed species resistant to that drug.…”
Section: Introductionmentioning
confidence: 99%
“…However, repeated use of one herbicide in one field leads to the proliferation of weed species resistant to that drug. Based on this, in the conditions of the Tashkent region (Uzbekistan), methods of tillage processing and the use of new herbicides are considered to be very urgent issues [8][9][10].…”
Section: Introductionmentioning
confidence: 99%